Mainstreaming Physical Infrastructure in Early Childhood Education and its Influence on Participation Rates in Public Primary Schools in Embu County, Kenya - Muthanje, Anastasia Kamwitha (Journal of Education and Training, 2022)
Early Childhood Education is crucial to the holistic growth of zero to eight years old children. This growth and development can to a large extent be realized through the provision and use of appropriate physical infrastructure. This study aimed to find out the status of Early Childhood physical infrastructure and how it influences participation rates, an aspect of internal efficiency in Public Primary Schools. Using stratified and simple random sampling techniques to get 39 public primary schools from 5 sub-districts; 39 primary headteachers, 156 primary teachers, and 39 ECE teachers. The study used a correlation design and collected data using questionnaires, a documentary analysis guide, and observation schedules. Data were analyzed using SPSS. Results were presented using percentages, frequencies, means, standard deviations, and inferential statistics of Pearson correlation. Results showed that there was a positive correlation between physical infrastructures such as kitchens, toilets for boys and girls, classrooms that are well ventilated, playgrounds, sports facilities, strong tall fences, furniture in good condition, and water points and internal efficiency (r=0.653, n=37, p<.05). The study concludes that there is a positive correlation between physical infrastructure and participation rates. There is a need for the county government in partnership with headteachers and parents to provide adequate physical infrastructure in Early Childhood Education.